2021
DOI: 10.1016/j.reprotox.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 2018 Camp Fire on birth outcomes in non-human primates: Case-control study

Abstract: The November 2018 Camp Fire, a devastating wildfire in Northern California, occurred during the peak of breeding season for field monkeys at the California National Primate Research Center (CNPRC). Effects of environmental stressors, such as wildfires, on birth outcomes in primates, and in humans, are poorly understood. Additionally, wildfires are of growing concern due to their increasing frequency and severity. The objective was to examine the impact of wildfire smoke on fertility, timing of birth, and pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…PM 2.5 also contains a mixture of metals, organic carbon, potassium, geologic material, and potentially ammonium nitrate 6 making it an ideal proxy measure for damage that can be caused by WFS. Because large number of structures (almost 19,000) were destroyed in the Camp Fire, including most of the town of Paradise, the smoke from this fire contained an unusual mixture of components:; Willson et al 7 reported high levels of phthalates, and a recent report by the California Air Resources Board 6 found significantly elevated levels of lead and zinc in the Camp Fire smoke associated, presumably, with the combustion of anthropogenic objects, such as houses, cars, and other objects containing plastics. Recent evidence suggests wildfire smoke (WFS) may also contain infectious microbes 8 .…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 also contains a mixture of metals, organic carbon, potassium, geologic material, and potentially ammonium nitrate 6 making it an ideal proxy measure for damage that can be caused by WFS. Because large number of structures (almost 19,000) were destroyed in the Camp Fire, including most of the town of Paradise, the smoke from this fire contained an unusual mixture of components:; Willson et al 7 reported high levels of phthalates, and a recent report by the California Air Resources Board 6 found significantly elevated levels of lead and zinc in the Camp Fire smoke associated, presumably, with the combustion of anthropogenic objects, such as houses, cars, and other objects containing plastics. Recent evidence suggests wildfire smoke (WFS) may also contain infectious microbes 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon was seen in rhesus macaques at the California National Primate Research Center (CNPRC), only a mile away from where our recipients were housed. The rate of pregnancy loss in rhesus macaques exposed to the Camp Fire was almost double that of controls 29 . Although the miscarriage rate seen at the CNPRC (18%) was not as high as was seen in our recipients (50%), it is still possible the Camp Fire played a role in the fetal losses experienced in ET2.…”
Section: Discussionmentioning
confidence: 84%
“…These may include the cytotoxic effects of inhalation of oxygen-free radicals [ 78 ], or the disruption of fetal–maternal circulation [ 79 ], which have been shown to result in low birth weights and other poor birth outcomes [ 80 ]. A recent study reported miscarriage in Rhesus macaques naturally exposed to wildfire smoke, further supporting the need to expand research of these reproductive impacts of smoke on animals [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at the University of California, Davis, recently published a study on cats hospitalized with burns and smoke inhalation following the 2017–2018 California wildfires; the cats were shown to have significant cardiovascular changes based on serial echocardiograms [ 53 ]. Rhesus macaques housed at the California National Primate Research Center and naturally exposed to wildfire smoke were reported to have pregnancy losses following heavy smoke exposure [ 54 ]. Additionally, early data suggests that immune suppression may be evident in macaques even 12 years following smoke exposure [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation